Application of Nightingale's Environmental Theory: The Effect of Heliotherapy on The Clinical Improvements in Individuals with Tuberculosis - Liza Wijaya; Sri Nabawiyati Nurul Makiyah (Jurnal Ilmiah Kesehatan, 2021)
Tuberculosis is a global health problem. Sunlight can trigger vitamin Dproduction, so it increases the immunity system. This study analysesNightingale's environmental theory through the effect of heliotherapy on theclinical improvements in individuals with tuberculosis. It was a quantitativestudy using a quasi-experimental design with a pretest-posttest approach and acontrol group. In addition, the population was 59 individuals with tuberculosisin Depok Sleman District, Yogyakarta. Meanwhile, there were 24 respondentsby purposive sampling method. The intervention group at Depok 3 Public Health Centre (PHC) was 17 respondents with heliotherapy and anti-tuberculosis drugs, while the control group at Depok 2 PHC was 17 respondents with anti-tuberculosis drugs. The independent variable washeliotherapy, while the dependent variable was the clinical improvementsconsisting of weight, cough, and shortness of breath. Heliotherapy wasconducted for four weeks with an intensity of four times a week for 25minutes a day. Instruments used weigh scale, Borg Scale, and Leicester cough questionnaire. In addition, data analysis used the Wilcoxon Test and paired T-Test with a significance of 0.05. The results showed that there were clinical improvements in the intervention group (p=0.000). In addition, there wereincreased clinical improvements in weight and cough scores in the controlgroup (p=0.000). However, there was no significant difference in the shortnessof breath score in the control group (p=0.06). In conclusion, the application ofNightingale's environmental theory through heliotherapy affects clinicalimprovements in individuals with tuberculosis.